Keanekaragaman Jenis Makrozoobenthos di Sungai Aek Buru - Eli Suryani; Arman Harahap (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the physical and chemical factors that contribute to the diversity of macrozoobentos in the Aekburu River, NA XI-X District, and North Labuhan Batu Regency. A descriptive approach was used to study the diversity of macrozoobentos in the Aek Buru River, Batu Tunggal Village, NA IX-X District, North Labuhan Batu Regency, and North Sumatra. The results showed that macrozoobenthic species were found in the Aek Buru River, with 15 species of the phylum Mollusca, and the highest relative abundance value was in the species Nerita albicilla at Station 1, with a percentage of 7.447%. From this study, it can be concluded that the abundance of macrozoobentos, diversity index, uniformity index, and dominance index are the types of macrozoobentos found.